Scale testing of students using remote technologies - Krasiuk Ю.М.; Shabalina І.В. (Journal of Information Technologies in Education (ITE), 2007)
With the purpose of adequate and operative verification of students’ readiness to productive educational activity in the process of learning economic informatics it is expedient to using the possibilities of indirect WebCT learning system. Results of entrance testing within the limits of a school rate of computer science of first-year students of economic specialities confirm the necessity of organization of process of teaching an economic informatics in accordance with the differentiated approach.